Eksistensi Ojek Konvensional Pada Era Digitalisasi di Jl. H. Imam Munandar, Pekanbaru - Sari Romaida Sihite; Teguh Widodo (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The conventional Ojek which is a non-online means of transportation that uses motorcycles and still exists to this day. In the midst of today's sophistication of digitalization, this research focuses on conventional eye-driving strategies. The aim of this study was to identify the various tactics used by conventional blind drivers, as well as the reasons why they still exist and operate. This research uses a descriptive qualitative approach with purposive sampling. Based on current criteria, the study involved five informants out of five drivers. The place of research is J.H. Imam Munandar, Pekanbaru. Observations, interviews, and documentation are used as data instruments. Research shows that conventional eye drivers use three strategies: an active strategy, a passive strategy, and a networking strategy. The study also suggests that conventional car drivers still survive due to incomes, social and hard-to-seek jobs today.